PENERAPAN TEKNOLOGI TEPAT GUNA UNTUK MENGATASI SAMPAH ORGANIK DAN AN-ORGANIK GUNA MENDUKUNG GREEN EKONOMI DI PKK ASOKA DI KOTA TANGERANG - Meidiyustiani, Rinny; Putri Suryandari; Setyani Dwi Lestari; Eryco Muhdaliha; Panca Maulana (Nirta Learning Centre, 2025)
PKK Asoka, located on Karyawan Street 3, RT 002/RW 09, Karang Tengah, Cileduk, Tangerang, faced issues with the accumulation of organic waste such as vegetable scraps and fruit peels, as well as plastic waste, leading to an unclean environment and unpleasant odors that could cause disease. The main challenges were the lack of knowledge and facilities for proper waste management. The PKM team from Budi Luhur University (UBL) conducted observations and provided assistance in applying appropriate technology. Residents were trained to process organic waste using a composter to produce liquid fertilizer through fermentation. Meanwhile, inorganic waste was recycled into valuable items such as wallets and trash bins that could be sold. The PKM team also provided training in financial recording and sales techniques, and introduced a smart financial application to help PKK Asoka record transactions and prepare financial reports. As a result, the community became more environmentally conscious, gained the ability to manage waste independently, and increased their income by utilizing waste materials, contributing to the realization of a Green Economy in their neighborhood.